Transition to propofol after sevoflurane anesthesia to prevent emergence agitation: a randomized controlled trial. Issue 5 (13th January 2015) - Costi, David; Ellwood, James; Wallace, Andrew; Ahmed, Samira; Waring, Lynne; Cyna, Allan; Anderson, Brian
Summary Background Emergence agitation (EA) is a common behavioral disturbance after sevoflurane anesthesia in children. Propofol 1 mg·kg−1 bolus at the end of sevoflurane anesthesia has had mixed results in reducing the incidence of EA, whereas propofol infusion throughout anesthesia maintenance seems effective but is more complex to administer. If a simple, short transition to propofol anesthesia was found to be effective in reducing EA, this could enhance the recovery of children following sevoflurane anesthesia. We therefore aimed to determine whether transition to propofol over 3 min at the end of sevoflurane anesthesia reduces the incidence of EA in children. Methods In this prospective randomized controlled trial, 230 children aged 1–12 years, undergoing magnetic resonance imaging (MRI) scans under sevoflurane anesthesia were randomized to receive either propofol 3 mg·kg−1 over 3 min (propofol group), or no propofol (control group), at the end of sevoflurane anesthesia. EA was assessed by a blinded assessor using the Pediatric Emergence Anesthesia Delirium (PAED) scale and the Watcha scale until 30 min after emergence. EA on the PAED scale was defined as a PAED score >12. EA on the Watcha scale was defined as a score ≥3. Times to emergence, postanesthesia care unit (PACU) discharge, and discharge home were also recorded. Results Data were analyzed for 218 children. The incidence of EA was lower in the propofol group on both PAED (29% vs 7%; relative risk = 0.25; 95% confidence interval 0.12–0.52; P < 0.001) and Watcha (39% vs 15%; relative risk = 0.37; 95% confidence interval 0.22–0.62; P < 0.001) scales. Duration and severity of EA were also reduced in the propofol group. Preplanned subgroup analyses for midazolam premedication, preexisting cognitive or behavioral disturbance, and age group did not alter our findings. Emergence time and time in PACU were both increased by a mean of 8 min in the propofol group (P < 0.001) with no difference in time to discharge home. Conclusions Transition to propofol at the end of sevoflurane anesthesia reduces the incidence of EA and improves the quality of emergence. There is a small increase in recovery time, but no delay in discharge home.